Synthesis, kinetics of photo-dimerization/photo-cleavage and physical properties of coumarin-containing branched polyurethanes based on polycaprolactones - R. Seoane Rivero; P. Bilbao Solaguren; K. Gondra Zubieta; L. Peponi; A. Marcos-Fernandez (eXPRESS Polymer Letters, 2016)
A series of coumarin-containing branched polyurethanes based on polycaprolactones, hexamethylene diisocyanate and a monohydroxylated coumarin monomer with 5 and 10% content by weight of coumarin units were successfully prepared. Chain architecture was controlled by combination of polycaprolactone (PCL) triol or tetrol with PCL diol. Terminal coumarin units segregated from the polyurethane matrix as measured by differential scanning calorimetry (DSC). Photo-dimerization with 313 nm lamps presented an anomalous behavior in two steps with high irreversibility at high conversions. Photo-dimerization/photo-cleavage reactions showed an increase in irreversibility with the increase in cycles. It was demonstrated that conversion measured by Raman spectroscopy gave the same results than conversion measured by ultraviolet (UV) spectroscopy. Photo-dimerization produced an elastomeric material with much better mechanical properties than non-irradiated material as a consequence of the crosslinking produced. Photo-cleavage decreased the mechanical properties and repeated photo-dimerization increased mechanical properties again.